Transcriptome Changes Reveal the Molecular Mechanisms of Humic Acid-Induced Salt Stress Tolerance in Arabidopsis - Joon-Yung Cha; Sang-Ho Kang; Myung Geun Ji; Gyeong-Im Shin; Song Yi Jeong; Gyeongik Ahn; Min Gab Kim; Jong-Rok Jeon; Woe-Yeon Kim (Molecules, 2021)
Humic acid (HA) is a principal component of humic substances, which make up the complex organic matter that broadly exists in soil environments. HA promotes plant development as well as stress tolerance, however the precise molecular mechanism for these is little known. Here we conducted transcriptome analysis to elucidate the molecular mechanisms by which HA enhances salt stress tolerance. Gene Ontology Enrichment Analysis pointed to the involvement of diverse abiotic stress-related genes encoding HEAT-SHOCK PROTEINs and redox proteins, which were up-regulated by HA regardless of salt stress. Genes related to biotic stress and secondary metabolic process were mainly down-regulated by HA. In addition, HA up-regulated genes encoding transcription factors (TFs) involved in plant development as well as abiotic stress tolerance, and down-regulated TF genes involved in secondary metabolic processes. Our transcriptome information provided here provides molecular evidences and improves our understanding of how HA confers tolerance to salinity stress in plants.